2015
DOI: 10.1111/cod.12486
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐hapten antibodies in response to skin sensitization

Abstract: SummaryWhereas T lymphocyte (T cell) activation is the key event in the acquisition of skin sensitization and subsequent elicitation of allergic contact dermatitis, the humoral component of immune responses to organic contact allergens has received little consideration. There is evidence that, in experimental animals, topical exposure to potent contact allergens is associated with B cell activation and proliferation, and hapten-specific antibody production. However, there is very limited evidence available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 90 publications
0
13
0
1
Order By: Relevance
“…4-ethoxymethylene-2-phenyl-2-oxazol-5-one (referred to as oxazolone; Figure 1A) has been widely utilized in models of contact hypersensitivity and, when applied to the mucosa, has been proposed to cause colitis through its properties as a hapten (Gorbachev and Fairchild 2001). However, to date, there is limited evidence for hapten-specific antibody production or responses following topical oxazolone sensitization or hapten-modified autologous proteins or luminal antigens identified at mucosal sites (Singleton et al, 2016; Wirtz et al, 2007). Interestingly, upon analysis of previously published microarray studies derived from epithelial-enriched colon fractions following intra-rectal oxazolone challenge (Olszak et al, 2014), we observed decreased expression of Mttp /MTP and increased expression for elements associated with AhR signaling, including P450 enzymes ( cyp1a1 ) and indoleamine 2,3-dioxygenase ( Ido1 ).…”
Section: Resultsmentioning
confidence: 99%
“…4-ethoxymethylene-2-phenyl-2-oxazol-5-one (referred to as oxazolone; Figure 1A) has been widely utilized in models of contact hypersensitivity and, when applied to the mucosa, has been proposed to cause colitis through its properties as a hapten (Gorbachev and Fairchild 2001). However, to date, there is limited evidence for hapten-specific antibody production or responses following topical oxazolone sensitization or hapten-modified autologous proteins or luminal antigens identified at mucosal sites (Singleton et al, 2016; Wirtz et al, 2007). Interestingly, upon analysis of previously published microarray studies derived from epithelial-enriched colon fractions following intra-rectal oxazolone challenge (Olszak et al, 2014), we observed decreased expression of Mttp /MTP and increased expression for elements associated with AhR signaling, including P450 enzymes ( cyp1a1 ) and indoleamine 2,3-dioxygenase ( Ido1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, lettuce may induce reactions through both immediate (humoral), intermediate (protein contact dermatitis) and delayed (T‐cell‐mediated) mechanisms, and the contribution of each of these in systemic reactions has not been clarified. Furthermore, experimental studies have even suggested that topical exposure to strong contact allergens may be associated with hapten‐specific antibody production, and more than one mechanism may therefore be involved .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that occupational exposure was the source of sensitization. The association between type I and type IV reactions may also be explained, as suggested by Singleton et al , by the production of anti‐hapten antibodies through skin sensitization. In humans and experimental models of skin sensitization, it has been shown that Th1 and Th2 cells may help B cells to produce antibodies, including IgE.…”
Section: Discussionmentioning
confidence: 89%